Novo sensor de amônia à base de polianilina modificada para controle de qualidade de produtos cárnicos - SANTOS, Djanira Rubim dos (2020)
Meat products tend to decompose quickly, which often causes eating disorders in those who consume them. For this reason, it is important to monitor, during storage, the formation of ammonia, which characterizes the stage of product decomposition. The present work aimed to develop a sensor based on polyaniline films, aimed at detecting ammonia in these types of foods. To this end, the synthesis and characterization of polyaniline were performed, using aniline and (NH4) 2S2O8 in an acid medium. Nickel phthalocyanine (NiPc) was added as a modifier to the synthesized polymer. 10, 20 and 30 bilayer films were assembled using the layer-by-layer (LbL) self-assembly technique and then evaluated using infrared (IR), UV-Vis and impedance spectroscopic techniques and cyclic voltammetry. (VC) and square wave (VOQ). The obtained results showed that the absorbance of light for the films of 10 bilayers (601 nm), 20 bilayers (607 nm), 30 bilayers (610 nm), gradually increases with the deposition of layers in the electrode. The cyclic voltamograms of the films confirmed the peak redox pairs characteristic of Pani and the displacement to the peak oxidation potential when the number of bilayers increased, showing the interaction of the polymer with the NiPc. The current change reflected a linear response to the ammonia released in the fish deterioration process, R2 = 0.981, I = (2.53 x 10-6) + (1.064 x 10-5) x at room temperature, demonstrating good sensitivity. Through this study it is possible to develop an electrochemical sensor with high sensitivity and also a pH indicator film that produces reliable responses to the pH variation in the fish deterioration process.